2019
DOI: 10.1007/s42044-019-00038-x
|View full text |Cite
|
Sign up to set email alerts
|

New hybrid method for feature selection and classification using meta-heuristic algorithm in credit risk assessment

Abstract: Credit risk is a factor that arises from the failure of the party to the contract. It is one of the most important factors of risk production in banks and financial companies. Still, there is no standard set of features or indices which have been declared through all credit institutions and according to the classification of customers, they are able to do through terms of credit value. In this paper, a meta-heuristic of imperialist competitive algorithm with modified fuzzy min-max classifier (ICA-MFMCN) is off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In turn, Figure 4 shows the countries where the articles included in this SLR were published. Again, most of them were published in China (33), followed by India (5). Table 4 details all the keywords retrieved from the selected documents.…”
Section: Total 660mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, Figure 4 shows the countries where the articles included in this SLR were published. Again, most of them were published in China (33), followed by India (5). Table 4 details all the keywords retrieved from the selected documents.…”
Section: Total 660mentioning
confidence: 99%
“…Different systems of this kind have been increasingly used, applying many current technologies. Several banks are developing their own systems based on their own selection criteria to reduce the probability of losses in loans requested by customers or firms [5]. Some of the most widely used CRA systems are based on Artificial Intelligence (AI) and Machine Learning (ML) techniques that analyze and pinpoint trends in potential debtors [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate how the mutation operator increases the exibility and effectiveness of the algorithm. Also, Nourmohammadi-Khiarak et al [40] produced a competitive algorithm to de ne an optimum subset of features, imperialist competitive algorithm with modi ed fuzzy min -max classi er (ICA-MFMCN) is given. Performance of the proposed classi cation ICA-MFMCN is approved and recognized a real credit set selected from a UCI dataset.…”
Section: Related Workmentioning
confidence: 99%
“…The utilization of metaheuristic algorithms such as the BBA for feature selection optimization problems is not new. Many studies reported the success of metaheuristic algorithms in solving combinatorial problems, as demonstrated in [10], [11]. There are many types of metaheuristic algorithms available for consideration that are categorized into four according to their search behaviors, which are evolution-based, swarm intelligence-based, physics-based, and human-related algorithms [12].…”
Section: Introductionmentioning
confidence: 99%